What We Talk about When We Talk about Gender-Inclusive Language: Teaching and Learning the Singular “They” in the First-Year Writing Classroom - Copland, Sarah (Discourse and Writing/Rédactologie, 2025)
As interest in the singular “they” has burgeoned in scholarly venues and mainstream media over the past decade, writing studies scholars remain surprisingly absent from these conversations. I studied the impact, value, and challenges of teaching this gender-inclusive pronoun in three sections of my institution’s first-year writing course. Prior to instruction on gender-inclusive language, students used the singular “they” liberally and were not aware of how gender-inclusive they were. After learning multiple gender-inclusive writing strategies, students indicated increased awareness of their own use of such language, interest and confidence in using it, and appreciation of its relevance. They preferred the singular “they” to other gender-inclusive writing strategies. But evidence of a disconnect between language use and ideological opposition to gender-inclusive language was also apparent in two (of 71) students’ work. In addition to their work, students’ self-assessments are therefore vital indicators of the value, impact, and challenges of teaching gender-inclusive language: the nexus of perceived use, interest, ability, and relevance drives whether students will transfer their learning to other contexts and reconcile the disconnect, if one exists, between their language use and ideological orientation towards such language. These findings may be relevant to teaching other forms of inclusive, bias-free language.